Determining features of the stressed state of a passenger car frame with an energy-absorbing material in the girder beam - Lovska, Alyona; Stanovska, Iraida; Nerubatskyi, Volodymyr; Hordiienko, Denys; Zinchenko, Olena; Karpenko, Nadiia; Semenenko, Yurii (Eastern-European Journal of Enterprise Technologies, 2022)
The object of this study is the processes related to the emergence, perception, and redistribution of loads in the improved structure of a passenger car frame. The scientific and applied task tackled in this paper is to ensure the strength of the supporting structure of a passenger car under operating loads. In this regard, it is proposed to improve the frame of a passenger car by constructing a girder beam from two rectangular pipes filled with material with energy-absorbing properties. The regularities of the frame load have been determined by taking into consideration the proposed solutions. It was found that the maximum equivalent stresses in the frame, taking its improvement into account, are 11.2 % lower than in the structure without filler, and 11.7 % lower than in the typical design. The results reported here are explained by the fact that the use of rectangular pipes filled with energy-absorbing material contributes to an increase in the moment of resistance of the frame, and, accordingly, reduces stresses. In addition, the study has determined the natural oscillation frequencies of the frame. The results of the calculation of the strength of the weld in the zone of interaction of the girder beam with the pivot beams are given. A feature of the results obtained is that the improvement in the strength of the frame is achieved not by strengthening its components but reducing the load. The scope of practical application of the reported results concerns railroad transportation, as well as other sectors of mechanical engineering. The conditions for the practical use of these findings are the introduction of closed profiles in the structure of vehicles at the stage of their design and modernization. This study could help reduce the cost of maintaining passenger cars and improve the efficiency of their operation. In addition, the research might prove useful for designing modern railroad car structures